Activated Ras/JNK driven Dilp8 in imaginal discs adversely affects organismal homeostasis during early pupal stage in Drosophila, a new checkpoint for development. - Ray, M.; Lakhotia, S.C. (Developmental Dynamics, 2019)
Dilp8-mediated inhibition of ecdysone synthesis and pupation in holometabolous insects maintains developmental homeostasis through stringent control of timing and strength of molting signals. We examined reasons for normal pupation but early pupal death observed in certain cases. Overexpression of activated Ras in developing eye/wing discs inhibited Ptth expression in brain via upregulated JNK signaling mediated Dilp8 secretion from imaginal discs, which inhibited ecdysone synthesis in prothoracic gland after pupariation, leading to death of ~25- to 30-hour-old pupae. Inhibition of elevated Ras signaling completely rescued early pupal death while post-pupation administration of ecdysone to organisms with elevated Ras signaling in eye discs partially rescued their early pupal death. Unlike the earlier known Dilp8 action in delaying pupation, hyperactivated Ras mediated elevation of pJNK signaling in imaginal discs caused Dilp8 secretion after pupariation. Ectopic expression of certain other transgene causing pupal lethality similarly enhanced pJNK and early pupal Dilp8 levels. Suboptimal ecdysone levels after 8 hours of pupation prevented the early pupal metamorphic changes and caused organismal death. Our results reveal early pupal stage as a novel Dilp8 mediated post-pupariation checkpoint and provide further evidence for interorgan signaling during development, wherein a peripheral tissue influences the CNS driven endocrine function.